Developing Spreadable Peanut Butters Incorporated With the Encapsulated Potential Psychobiotic Lactococcus Lactis C19.1 Strain - Harsa, Hayriye Şebnem; Akkuş, Zeynep Aysun (01. Izmir Institute of Technology, 2023)
In recent years, the partially processed food market has increased, partly due to the demand for fresh-cut or dried products. However, there is an increasing demand for foods enriched with physiologically active ingredients such as probiotics and prebiotics. From the nutrional point view, these two functional factors, have created a new market area for fruit and snack products. Peanuts have high nutritional value (24% protein, 45% fat and 13% fiber) as well as high amounts of thiamine and niacin). It is also known to reduce the risk of prostate, liver, colon and lung cancer and stress-related diseases. In this study, as a model bacteria Lactococcus lactis C19.1 strain isolated from Turkish cottage cheese has been impregnated with peanut and cashew nut butter after encapsulation. In the selection of the Lactococcus lactis strain, porbiotic and anti-stress properties were considered. To increase the viability of the strain, the encapsulation was carried by whey protein-xylan complex as the wall material. After encapsulation, the probiotic strain was added to the peanut and cashew nut butter formulation. In addition, in order to determine the encapsulation efficiency, it was impregnated to the butters the free cell form. The results revealed that encapsulation increased the shelf life stability of the psychobiotic cell. The shelf life of the peanut butters containing free cell of L. lactis was determined as 30 days that of 45 days in encapsulated cell containing samples. In addition, in vitro analyzes revealed that encapsulation protected probiotic cells in simulated gastrointestinal system and, the viability was between 106 – 107 CFU/g. However, the viability rate was found to be 105 in fort he free cell containing samples after digestion test. Cashews and peanut butters containing encapsulated cell came to the fore, as 105 CFU/g remained below the 106 CFU/g, which is the condition of being probiotic.

Son yıllarda, kısmen işlenmiş gıda piyasası, kısmen taze kesilmiş veya kurutulmuş ürün talebine bağlı olarak artış göstermiştir. Bununla birlikte, probiyotik ve prebiyotikler gibi fizyolojik olarak fonksiyonel bileşenlerce zenginleştirilmiş gıdalara yönelik artan bir talep bulunmaktadır. Besinsel açıdan bakıldığında bu iki fonksiyonel faktör, bu tür bileşenlerle zenginleştirilmiş meyve ve çerez ürünleri için yeni bir pazar alanı oluşturmuştur. Fıstık yüksek besinsel değere (%24 protein, %45 yağ ve %13 lif) aynı zamanda yüksek miktarda tiamin ve niasin) sahip bir kuruyemiştir. Ayrıca prostat, karaciğer, kolon ve akciğer kanseri ve strese bağlı hastalık riskini azalttığı da bilinmektedir. Bu çalışmada, probiyotiklerin sağlık üzerindeki etkileri göz önüne alınarak fıstık ve kaju ezme formülasyonunda Türk çökelek peynirinden izole edilen model bakteri Lactococcus lactis C19.1’in serbest ve enkapsüle halde ilavesi gerçekleştirilmiştir. Probiyotik ve antistres özelikleri üzerinde yapılan çalışmaların yoğun olduğu Lactococcus lactis suşunun seçilerek ve stabilitesinin artırılması amacıyla peyniraltı suyu protein-ksilan kompleksi ile enkapsüle edilip fıstık ve kaju ezmelerine ilave edilmiştir. Ayrıca enkapsülasyon verimliliğinin belirlenmesi amacıyla serbest hücrelerde ezme formülasyonuna katkılanmıştır. Elde edilen bulgulara göre enkapsülasyon işleminin ezmelerin probiyotik raf ömrünü arttırdığı belirlenmiştir. Serbest hücre psikobiyotik eklenmiş fıstık ezmelerinin raf ömrü 30 günde kalırken, enkapsüle edilmiş psikobiyotik eklenen fıstık ezmelerinin raf ömrü 45 gün olmuştur. Ayrıca in vitro analiz sonuçlarına göre enkapsülasyon işleminin simüle sindirim ortamında probiyotik hücrelerin dayanımını artırdığı görülmüştür. Sindirim testi sonucunda enkapsüle probiyotik içeren fıstık ve kaju ezmelerinin canlılık seviyesi 106 – 107 KOB/g arasındatespit edilirken bu sayı serbest hücre içeren ezme örneklerinde 105 KOB/g seviyesine düşmüştür. 105 KOB/g, probiyotik olma koşulu olan 106 KOB/g’ın altında kaldığı için enkapsüle kaju ve fıstık ezmeleri öne çıkmıştır.
Enkapsüllenmiş potansiyel psikobiyotik Lactococcus lactis C19.1 suşu ilaveli sürülebilir fıstık ezmelerinin geliştirilmesi
Thesis (Master)--İzmir Institute of Technology, Food Engineering, Izmir, 2023
Includes bibliographical references (leaves. 61-74)
Text in English; Abstract: Turkish and English
Keywords: Lactococcus lactis; Probiotics; Psychobiotics; Peanut butter; GABA